Practical studies in Vero cell and Human amnion cells for viral and stem cell applications - Ahmed Mahfouz (International Journal of Vaccines, 2024)
Vero cells are one of the most popular mammalian continuous cells in molecular, cellular, and microbiological research. African green monkey kidneys are used to make these.One continuous cell line is the Vero cell line. This cell line is dependent on anchorage. Vero cells can be cultured in suspension because they are anchorage independent. Thought to be non-tumorigenic cells that came from a female Chlorocebus sabaeus Numerous viruses can infect vero cells. Its lack of interferon expression is thought to be one of the causes of this. When viruses infect cells, the signal peptide interferon is not produced, impairing the cell's ability to fight off infection. Second type of cell we focus on are human amnion cell which are embryonic stem cell that have ability to grow fast this stem cell can be targeted in regenerative medicine to treat colon cancer and other tumor types, we supposed that scientists can use Hu -amnion cells in drug discovery and gene editing by induce stem cell to form scaffold structure and tissue printing, also Hu-amnion cells can be seeded to be used in vaccine by vector mediated vaccine or small sub unit vaccine. Our research focuses on the separation of cells from different part using this cell in application of stem cell and viral replication and vaccine production.
Keywords: Human amnion cells; Vaccine production; Vero cells; Viral replication; stem cell therapy